The Influence of Differentiation, Product Quality, Targeting on Interest in Buying Lega Rantauprapat Drinks with Brand Positioning as a Moderating Variable - Sri Devi Ramadani; Yudi Prayoga; Elvina Elvina (PT Mattawang Mediatama Solution, 2023)
In this era of digitalization, competition for the food and beverage business is increasing rapidly. This can be seen from the many types of food and beverages available in the market. Even though the current situation is not very good due to the pandemic that occurred a few years ago, the number of business actors in Labuhanbatu is increasing. Culinary diversity opens opportunities for business actors in Labuhanbatu to develop their business as a means of serving drinks and food to the people in Labuhanbatu. Various targeting strategies are carried out such as market surveys about products that are most in demand by the community, affordable prices, locations that are suitable for the products being marketed, product marketing processes for all products from all levels of society, and how to provide services to consumers as well as the provision of facilities and infrastructure is a marketing process carried out to attract consumer buying interest. The variables to be examined in this study are Differentiation (X1), Product Quality (X2), Targeting (X3) as independent variables, and Purchase Intention (Y) as the dependent variable, and Brand Positioning (Y) as a moderating variable. The results of the normality test using the P-plot chart were carried out using the Kolmogorov-Smirnov analysis with the condition that Asmp. Sig.(2-tailed)> 0.05, it means that the normal distribution is not disturbed, whereas if the value of Asmp. Sig.(2-tailed) < 0.05, it means that the normal distribution is disturbed. And showing the results of the Kolmogrov-Smirnov statistical analysis in the table it can be seen that the Asymp Sig (2 tailed) value is 0.200 greater than 0.05.